1991
DOI: 10.1067/mva.1991.33214
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal artery aneurysms: A 25-year surgical experience

Abstract: Operative repair was undertaken for 51 popliteal aneurysms in 39 patients between 1958 and 1990. Operation was performed on an emergency basis in 19 extremities with limb-threatening ischemia and as an elective procedure in 32 extremities. Cumulative limb salvage (94%) rates and patency rates (67%) became significantly different at 6 years (p less than 0.05). Graft patency was affected by clinical presentation and runoff. After 1 year, cumulative patency for extremities with limb-threatening ischemia was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 9 publications
(2 reference statements)
5
81
0
Order By: Relevance
“…Unlike those involving the abdominal aorta, popliteal aneurysms are prone to thrombose and to lead to episodes of peripheral embolization (up to 69 % of the cases) (Fig. 19) [81,82,83]. Embolic events can arise massively and cause acute limb ischaemia or can occur chronically leading to progressive impairment of runoff.…”
Section: Dilatative Pathologymentioning
confidence: 99%
“…Unlike those involving the abdominal aorta, popliteal aneurysms are prone to thrombose and to lead to episodes of peripheral embolization (up to 69 % of the cases) (Fig. 19) [81,82,83]. Embolic events can arise massively and cause acute limb ischaemia or can occur chronically leading to progressive impairment of runoff.…”
Section: Dilatative Pathologymentioning
confidence: 99%
“…Nevertheless, some authors reported some cases of rupture of a previously ligated PAA [8,17]. This was uncommon, and it could be explained by the fact that patients died before the onset of the complication.…”
Section: Discussionmentioning
confidence: 99%
“…However, some cases of symptomatic enlargement and rupture of already excluded aneurysms have been reported [8,17]. The origin of this recurrence is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Elective popliteal aneurysm repair has 10-year patency rates between 66 and 92% and 10-year limb salvage rates from 93 to 100%. [12][13][14] When performed for limb-threatening ischemia, these grafts have 10-year patency rates of 39 to 60% and 10-year limb salvage rates between 79 and 84%. [12][13][14] While exclusion of the popliteal artery is clearly mandated when treating popliteal artery aneurysms, the same may not be true for popliteal arterial injury secondary to posterior knee dislocation.…”
Section: Discussionmentioning
confidence: 99%